1999
DOI: 10.1002/(sici)1097-4598(199904)22:4<497::aid-mus11>3.0.co;2-t
|View full text |Cite
|
Sign up to set email alerts
|

Relationships between clinical symptom severity scales and nerve conduction measures in carpal tunnel syndrome

Abstract: This study examined the severity of symptoms in carpal tunnel syndrome (CTS) in relation to nerve conduction measures of the median nerve. Clinical symptom severity and nerve conduction studies were evaluated for 64 hands with CTS in 45 patients. We found the following: (1) significant relationships identified among the clinical scales resulted in a dichotomous symptom classification scheme into primary and secondary symptoms, with the former being more specific for those symptoms usually seen in association w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
74
0
5

Year Published

2000
2000
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 131 publications
(89 citation statements)
references
References 6 publications
5
74
0
5
Order By: Relevance
“…According to the American Academy of Neurology practice parameters criteria, CTS is defined [12,13] as follows:…”
Section: Methodsmentioning
confidence: 99%
“…According to the American Academy of Neurology practice parameters criteria, CTS is defined [12,13] as follows:…”
Section: Methodsmentioning
confidence: 99%
“…All patients were subjected to full history taking, thorough clinical examination and neurological examination including (1) parathesia, pain provoked or worsened by sleep, sustained hand or arm position or repetitive action of the hand or wrist that is mitigated by a change in posture or by shaking of the hand (2) sensory deficit in median nerve distribution, (3) motor deficit of median innervated thenar muscles and (4) positive provocative tests for CTS (Tinel sign, Phalen test and Reverse Phalen test). The clinical diagnosis of CTSwas made when criterion 1 and one or more of criterion 2-4 were fulfilled [10,11]. Electrophysiological assessment of wrists and gray scale ultrasonography were done for all patients.…”
Section: Methodsmentioning
confidence: 99%
“…EDX findings have been positively correlated with patient symptom severity and negatively correlated with functional status [11,12]. One study, however, reported a negative correlation between EDX data and development of symptoms and diagnosis of CTS in industrial workers followed prospectively [13].…”
Section: Introductionmentioning
confidence: 99%
“…There is no universally accepted standard in classification of severity assessment of CTS. However, several electro diagnosticians use the AANEM minimonograph as their guideline [12,17]. In a previous study, clinical and EDX changes after surgery were evaluated in patients with "severe" CTS, and severity was defined based on EDX data [18].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation